Post-Jazz Poetics - Ryan, J. author. aut Link
XI, 225 p. 5 illus.
Keywords: African-American expressive arts draw upon multiple traditions of formal experimentation in the service of social change. Within these traditions, Jennifer D. Ryan demonstrates that black women have created literature, music, and political statements signifying some of the most incisive and complex elements of modern American culture. Post-Jazz Poetics: A Social History examines the jazz-influenced work of five twentieth-century African-American women poets: Sherley Anne Williams, Sonia Sanchez, Jayne Cortez, Wanda Coleman, and Harryette Mullen. These writers engagements with jazz-based compositional devices represent a new strand of radical black poetics, while their renditions of local-to-global social critique sketch the outlines of a transnational feminism.